Studying and enhancing the methods for distance teaching of computer science in Kazakh secondary school students during the pandemic - M. M. Zhamankarin; A. M. Sivinskiy; M. K. Aitkenova; M. B. Zhanibekov (Образование и наука, 2023)
Introduction. In 2020, the first two weeks of the enforced transformation of all the levels of school education, which was initiated as one of the measures against the Coronavirus disease (COVID-19), revealed a range of issues hampering the appropriate distance education. The absence of the methodological basis for conducting online classes in the Kazakh pedagogical community defined the need to study and enhance forms and technologies that would be efficient to use to interact with students during the transition of the national education system to distance education.Aim. The aim of this research lies in defining efficient methods for distance teaching of computer science in the Kazakh secondary school students in terms of ensuring the maintenance of the quality of knowledge and the academic progress of students at the sufficient level corresponding to that of the traditional in-person education.Methodology and research methods. A total of five educators and 320 students of three Kazakh schools took part in the study. At the moment of the experiment, the students were aged 12 to 18 years old. The participants were divided into seven groups according to the educational level (5th–11th forms) in order to make it more convenient to trace qualitative changes in the academic progress depending on the selected method for distance teaching of computer science. The authors conducted three control evaluations of the quality of knowledge in each of the 320 participants. The t-test for unpaired samples for every group was conducted to prove the statistical certainty of the calculated average reference values, which were required to confirm the viability of the conducted research. The analysis of the data obtained at the concluding stage of the experiment allowed to compare them with the reference values calculated at the preliminary stage of the research in question. For the comparison, The authors applied the Mann–Whitney U test for independent samples.Results. The preliminary analysis of the quality of knowledge related to the discipline of computer science in the participants revealed generally high and average level of both acquisition of theoretical information and development of the subject-related skills, which was registered based of the results of in-person education. The leading experience of the specialists composing the authors’ initiative research group allowed developing a structural scheme for an online lesson. The lessons applying this scheme were conducted up to the end of the academic quarter. By conducting the Mann–Whitney U test, we discovered that the obtained average values of the quality of teaching computer science to the participants statistically increased (I group – Uemp = 6.49 (p ≤ 0.05), II group – Uemp = 7.46 (p ≤ 0.05), III group – Uemp = 6.05 (p ≤ 0.01), IV group – Uemp = 6.71 (p ≤ 0.05), V group – Uemp = 6.91 (p ≤ 0.01), VI group – Uemp = 6.65 (p ≤ 0.05), VII group – Uemp = 6.21 (p ≤ 0.05)). Despite temporary fall in the efficiency of teaching computer science registered during the transition to the distance model, it was managed to achieve the level of academic progress and acquisition of knowledge corresponding to that of in-person education.Scientific novelty. TThe significance of the collected and analysed data was statistically proved. The data confirmed the efficiency of the use of defined and adapted approaches and teaching techniques, which were able to compensate the absence of traditional in-person lessons, while preventing the fall in the academic progress and the quality of knowledge in students.Practical significance. The obtained results evidence the success of the arrangements aimed at the enhancement of the methods for distance teaching of computer science in the Kazakh secondary school students during the transition to distance education enforced due to the pandemic.